Morphological assessment of Stevia rebaudiana Bertoni accessions in IIUM's germplasm as initial material for stevia breeding - Othman, Halimaton Saadiah; Osman, Mohamad; Zainuddin, Zarina (International Network for Scientific Information Publication (INSI), 2015)
Background: Stevia rebaudiana Bertoni, belonging to the family Compositae, has a long and successful history of use as a commercial sweetening agent. It originated from Paraguay and was first introduced into Malaysia in 1970s. The sweetening agents are the steviol glycosides which are 150 to 350 times sweeter than sugar. Currently in IIUM’s germplasm collection, there are a total of 10 stevia accessions available which are collected from all across Malaysia. Objective: The key step before any effective breeding program can be initiated is by studying phenotypic diversity in a germplasm. Being an introduced species, the number of stevia accessions available is still small and therefore is inadequate for effective breeding purposes. In order to broaden its genetic base, introductions of exotic accessions have been made which include accessions from Paraguay and additional numbers of accessions collected across Malaysia. Morphological evaluation on these seventeen stevia accessions is substantial as the jumping base before further breeding process can be initiated. Results: All accessions are planted in an experimental plot at IIUM Kuantan, Pahang. Morphological evaluations include plant height, number of branches, number of leaves, leaf size and widest branch. From observation, results showed that accessions MS007 and MS012 have the most promising characteristics in term of plant height, number of leaves and leaf size which could be exploited for further breeding purposes. Conclusion: Morphological diversity observed in all seventeen stevia accessions in the germplasm showed a wide genetic variation which would be useful for future hybridization studies.